2020
DOI: 10.1167/iovs.61.11.5
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Cellular Mechanisms That Regulate the Sustained Contraction and Relaxation of the Mammalian Iris

Abstract: Purpose In mammals, pupil constriction and dilation form the pupillary light reflex (PLR), which is mediated by both brain-regulated (parasympathetic) and local iris-driven reflexes. To better understand the cellular mechanisms that regulate pupil physiological dynamics via central and local photoreception, we have examined the regulation of the PLR via parasympathetic and local activation, respectively. Methods In this study, the PLR was examined in mouse enucleated ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The eyeballs were enucleated and positioned in a centrifuge tube (5 ml) and fixed in 4% paraformaldehyde for immunohistochemistry; Additional eyeballs were enucleated, then the cornea, lens, and vitreous were quickly removed on ice. The retinas were snapped frozen in liquid nitrogen, and stored at −80°C ( Srinivasalu et al, 2018 ; Kole et al, 2020 ; Sghari et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The eyeballs were enucleated and positioned in a centrifuge tube (5 ml) and fixed in 4% paraformaldehyde for immunohistochemistry; Additional eyeballs were enucleated, then the cornea, lens, and vitreous were quickly removed on ice. The retinas were snapped frozen in liquid nitrogen, and stored at −80°C ( Srinivasalu et al, 2018 ; Kole et al, 2020 ; Sghari et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The size of the pupil varies with the intensity of incident ambient light, which forms the PLR. Generally, pupil dilation and constriction depends on both autonomic innervation and local reflexes [ 126 ]. Light incident into one eye can cause constriction of both the eyes, including the unstimulated eye.…”
Section: Physiological Effectmentioning
confidence: 99%
“…The efferent pathway includes the projection from the PON to the EWpg and ends up at the sphincter pupillae muscle, from where the postganglionic fibers release acetylcholine (ACh), which acts on the muscarinic receptors on the sphincter muscles and leads directly to pupillary constriction [ 139 ]. This physiological process is observed to be related to changes in extracellular Ca 2+ concentration and ryanodine receptor (RyR) channels in the iris sphincter muscle [ 126 ]. Pupillary dynamics depend on time, intensity of illumination, and the pupil shape in different species [ 128 ].…”
Section: Physiological Effectmentioning
confidence: 99%
“…However, ∼20 years ago, so-called atypical or non-visual opsins, including Opsin 3 ( Opn3 , also known as encephalopsin or panopsin), Opn4 (melanopsin), and Opn5 (neuropsin), were identified in photoreceptors that were not thought to be involved in visual perception directly ( Provencio et al, 1998 ; Blackshaw and Snyder, 1999 ; Tarttelin et al, 2003b ). Of these three opsins, melanopsin has been the most studied in terms of function in visual and non-visual light detection processes, where it has been shown to play a key role in circadian clock photoentrainment and pupillary constriction in mammals ( Freedman et al, 1999 ; Lucas et al, 2003 ; Xue et al, 2011 ; Sghari et al, 2020 ). Other known non-visual effects of Opn4 include DNA repair activation ( Hirayama et al, 2009 ) and cell cycle regulation ( Dekens et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with reported light-regulated processes other than vision, the presence of atypical photopigments in multiple non-retinal adult tissues has been observed. For example, Opn4 has been detected in melanocytes ( Provencio et al, 1998 ), the iris ( Xue et al, 2011 ; Sghari et al, 2020 ), cornea and associated trigeminal ganglia ( Delwig et al, 2018 ), blood vessels and heart ( Regard et al, 2008 ; Sikka et al, 2014 ), and Opn5 being found in the eye, brain, testes, ear, and skin ( Kojima et al, 2011 ; Buhr et al, 2015 , 2019 ; Haltaufderhyde et al, 2015 ). The initial identification and expression of Opn3 in the adult mouse brain, including regions like the cerebral cortex and cerebellum ( Blackshaw and Snyder, 1999 ), have been verified and extended ( Nissilä et al, 2012 ; Olinski et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%